Experiential Marketing and Generation Z Customer Loyalty in Culinary MSMEs - Lalitya Paramartha; Roslina; Faila Shofa (International Journal of Business and Quality Research, 2026)
The increasing competition in the culinary industry has encouraged business owners to focus not only on product quality and pricing strategies, but also on creating memorable customer experiences. This research seeks to examine the influence of experiential marketing dimensions composed of sense, feel, think, act, and relate toward Generation Z customer loyalty in culinary MSMEs. The research applied a quantitative approach using a survey method through questionnaire distribution to respondents selected through purposive sampling. The study utilized multiple linear regression to examine the collected data following the fulfillment of validity, reliability, and classical assumption requirements. The results demonstrate that all dimensions of experiential marketing indicate positive and significant effects on customer loyalty. Among the five dimensions, feel emerged as the most dominant factor affecting customer loyalty, while act showed the lowest effect. The findings also reveal that Generation Z customer loyalty tends to be stronger at the conative loyalty stage than at the action loyalty stage. Furthermore, experiential marketing contributed substantially to customer loyalty, while the remaining percentage was affected by other variables beyond the scope of this study. The findings support the experiential marketing concept introduced by Schmitt (1999) and the experiential value theory developed by Holbrook (1999), particularly within the context of local culinary MSMEs. This research suggests that culinary business owners should strengthen emotional experiences, customer engagement, and social interaction to maintain sustainable customer loyalty.